Territorial Expropriation, Pandemic, and Resistance: Indigenous Movements and Policies in Southeastern Pará - Possas, Hiran de Moura (2024)
In the COVID-19 pandemic, indigenous peoples in the southeast of Pará faced, among many emergencies, the worsening of territorial violations and precarious health care and education, without depriving them of resilience to frontier capitalism in the region. The information obtained through interviews with indigenous leaders, consultation of official data and those published by the Articulation of Indigenous Peoples of Brazil (APIB), as well as field notes on the performance of the Mutual Support Network to Indigenous Peoples of Southeastern Brazil Pará, highlights the strategic use of the territory for isolation and resurgence of cultural practices, and the formulation of policies to resist the systemic crises aggravated by the fascist national government of the period.